Factores de riesgo asociados al incumplimiento del control prenatal en mujeres de 14 a 25 años - Centro de Salud Urbano Cayambe. - Cheza Pantoja, Brayan Alexander (2024)
Prenatal attention care allows to evaluate the health and nutrition condition of pregnant women and to detect early stages of possible complications or factors that may influencenegatively the pregnancy period; thus, the main objective of this research is to develop anaction plan to improve the level of attendance to prenatal controls among pregnant women. This research is an observational type, with a descriptive design, and transversal.The application of the instrument to gather the information of quantitative data was addressed to women who attend the urban health center in Cayambe. From the populationsurveyed, 37% of pregnant women are between 17 and 19 years old, 47% of women aresingle, 52% of pregnant women claimed to attend between 4 and 6 medical controls, 53% do not attend prenatal controls due to working reasons or lack of information; 44% of thewomen claimed to have difficulties for commuting to the health center, and 59% claimedto have sometimes family or her partner’s support. In this research the factors that influence negatively the attendance of pregnant women are the lack of knowledge, socio-cultural and demographic barriers, therefore this leads to the implementation of educational activities to improve the quality of the mother and child binomial.